2015
DOI: 10.2139/ssrn.2548959
|View full text |Cite
|
Sign up to set email alerts
|

Robust Sparse Canonical Correlation Analysis

Abstract: Background: Canonical correlation analysis (CCA) is a multivariate statistical method which describes the associations between two sets of variables. The objective is to find linear combinations of the variables in each data set having maximal correlation. In genomics, CCA has become increasingly important to estimate the associations between gene expression data and DNA copy number change data. The identification of such associations might help to increase our understanding of the development of diseases such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…S5A). We considered a maximum of 𝑐𝑐𝑟𝑟𝑟𝑟𝑟𝑟 =10 canonical variates as in other high-dimensional data (38). We extract first 𝑘𝑘 canonical variates that maximize the ratio 𝜑𝜑 � 𝑗𝑗 = 𝜌𝜌 � 𝑗𝑗 /𝜌𝜌 � 𝑗𝑗+1 over the set of 𝑗𝑗 = 1, … , 𝑐𝑐𝑟𝑟𝑟𝑟𝑟𝑟 − 1.…”
Section: Discussionmentioning
confidence: 99%
“…S5A). We considered a maximum of 𝑐𝑐𝑟𝑟𝑟𝑟𝑟𝑟 =10 canonical variates as in other high-dimensional data (38). We extract first 𝑘𝑘 canonical variates that maximize the ratio 𝜑𝜑 � 𝑗𝑗 = 𝜌𝜌 � 𝑗𝑗 /𝜌𝜌 � 𝑗𝑗+1 over the set of 𝑗𝑗 = 1, … , 𝑐𝑐𝑟𝑟𝑟𝑟𝑟𝑟 − 1.…”
Section: Discussionmentioning
confidence: 99%
“…For datasets with a very large number of reference and/or target traits (i.e. p ≫ n ), sparse canonical correlation analysis (Witten and Tibshirani 2009; Wilms and Croux 2016) may reduce over-fitting, but this situation is not common when relating two sets of traits U and V that contain organism-level phenotypes as opposed to molecular features.…”
Section: Resultsmentioning
confidence: 99%
“…We anticipate that the framework outlined in this study will be increasingly useful as studies of diverse, genetically unique populations become more widespread. A useful future extension to this approach would incorporate statistical techniques such as sparse canonical correlation analysis (Witten and Tibshirani 2009; Wilms and Croux 2016), which could permit inference in phenome-level studies where the target or reference traits are high dimensional. Overall, our approach is likely to be particularly important in functional genomics studies, those utilizing post-mortem subjects, and large population studies in which individuals are unavailable for further characterization.…”
Section: Discussionmentioning
confidence: 99%
“…The techniques introduced by Waaijenborg, Verselewel de Witt Hamer, and Zwinderman (), Parkhomenko, Tritchler, and Beyene (), and Witten et al () impose covariance restrictions. Wilms et al () suggested that variables are selected (find a sparse solution) using a penalized regression framework. Wilms et al () demonstrated that this method outperforms CCA and some other sparse CCA approaches in almost all simulated scenarios.…”
Section: Methodsmentioning
confidence: 99%
“…Wilms et al () suggested that variables are selected (find a sparse solution) using a penalized regression framework. Wilms et al () demonstrated that this method outperforms CCA and some other sparse CCA approaches in almost all simulated scenarios. This methodology is freely available in package “PMA” in R on CRAN, and we chose to use it for the analyses in this study.…”
Section: Methodsmentioning
confidence: 99%